Employment Protection Legislation and Mismatch: Evidence from a Reform - Fabio Berton; Francesco Devicienti; Sara Grubanov-Boskovic (Institute of Labor Economics (IZA), 2017)
Liberalization of temporary contracts has been a hallmark of labor market reforms during the last decades. More recently, factors like the sovereign debt crisis pushed the most indebted countries to unprecedented reductions of employment protection legislation (EPL) also on open-ended contracts. These policies are justified under the assumption that EPL harms the allocation of workers on the jobs where they are most productive. How EPL affects the quality of job matches is nonetheless an underexplored issue. In this paper, we provide new evidence that exploits exactly one of these recent reforms, the so-called Fornero Law, introduced in Italy in 2012 in the background of austerity reforms. Results show that good matches have increased. Further, the reduction in EP favored labor reallocation. Eventually, it was also followed by an increase in productivity, albeit small. While the results are consistent with the economic theory that informed deregulation, we highlight caveats and limitations.
Keywords: J24; J63; 330; employment protection legislation; turnover; mismatch; productivity; Fornero Law; difference-in-differences